Immobilized phosphotungstic acid based ionic liquid: Application for heterogeneous esterification of palmitic acid. (15th March 2018) - Wang, Yongqiang; Zhao, Dan; Wang, Lulu; Wang, Xianqin; Li, Lujun; Xing, Zhongpeng; Ji, Na; Liu, Shejiang; Ding, Hui
Highlights: Phosphotungstic acid was immobilized on SBA-15 through chemical approach. A double bond-functionalized zwitterion was employed as the media for immobilization. A high esterification yield of 88.1% was obtained under mind conditions. The catalyst can be recovered conveniently and reused for more than 5 times. Abstract: For biodiesel production from waste oils, the esterification pretreatment process is now recognized as one of the most important approaches to convert free fatty acids for improving the quality of waste oils. In this paper, before immobilizing, three environmentally friendly acid ionic liquids were selected to conduct the immobilization. 1-(3-sulfonate)-propyl-3-allylimidazolium hydrogen sulfate, trifluoromethanesulfonate and dihydrogen phosphotungstate ionic liquids were prepared and characterized by NMR. All the three ionic liquids had the capacity to catalyze esterification of palmitic acid with yields of more than 98%. Therefore, the ionic liquids were supported on functionalized SBA-15 by thiol-ene click reaction. The immobilized ionic liquids were characterized by SEM, FTIR, NMR, XRF, and BET. Because of the strong acidity of phosphotungstic acid and the high loading rate (41.2%), 1-(3-sulfonate)-propyl-3-allylimidazolium phosphotungstate supported ionic liquid was proved to possess the highest catalytic performance which gave a 88.1% esterification yield after 8 h when the reaction temperature, methanol to acid molar ratio and catalyst dosage were 65 °C, 9 and 15 wt%, respectively. In addition, the supported ionic liquid could be reused for 5 times without significant deactivation.